First-Principles Study of Metal Impurities in Silicon Carbide: Structural, Magnetic, and Electronic Properties - Zhang, Lin; Cui, Zhen (Frontiers in Materials, 2022)
The configurations of 10 types of metal-doped silicon carbide (SiC) systems were investigated by the first-principles calculations. The dopants include eight types of 3d-series transition metal atoms, one semi-metal Ge atom, and one other metal Al atom. For all the metal-doped SiC systems, the steadiest doping sites are fixed at the substituted Si site, while the Ti-SiC system exhibits the most potent binding activity. The properties of these new systems vary with the doping atoms. The SiC- and Al-SiC systems convert to magnetic metals. The Ti- and Ge-SiC systems remain non-magnetic semiconductors, while the V-, Cr-, Mn-, Fe-, Co-, and Zn-SiC systems turn into magnetic semiconductors with magnetic moments related to the valence electron number of dopants. Partial charge transfers from the metal atoms to the adjacent C atoms accompanied the change in the electron-emitting capacity of the new systems. The work function achieves the minimum of 3.439 eV in the Co-SiC system, just 71.6% of the original SiC system. Our analysis indicates that the potent binding energy of the Ti-SiC system is due to the complete bonding states between the transition metal Ti and the adjacent C atoms. The magnetism evolution in semiconducting metal-doped SiC is attributed to the occupation mode of the hybridization orbitals nearby the Fermi level, which are determined by the coupling of the 3d orbital of transition metal atoms and the defect states of the vacancy atoms. The adjustable magnetic and electronic properties of the metal-doped SiC systems provide a flexible method in designing more suitable SiC-based spintronics and field electron-emitting devices.